THE IMPLEMENTATION OF COUNSELING COLLABORATIVE BASED LEARNING TO IMPROVE STUDENTS’ CREATIVE THINKING ABILITY (A CASE STUDY ON SPECIAL NEEDS EDUCATION STUDENTS IN UNINUS) - Husen Saeful Insan (Kopertis Region IV Jabar and Banten, 2019)
There are many factors that influence the less successful learning activity in special needs education study program at UNINUS. Those factors among others lecturer still not maximize students’ creative thinking abilities, lack of attention to students’ capabilities and experiences, less attention to students’ complaints related to learning, less in valuing students’ opinions and less recognizing and strengthen students’ positive actions. Therefore, it is necessary to develop learning model that can improve students’ creative thinking ability. This study is trying to develop the learning model based on collaborative counseling that will be done in three years. The purpose of this first year study is to make draft of a model that has been tested its feasibility. To achieve the objectives,the researcher implement Research and Development design through these following stages:preliminary study, designing hypothetical model, testing the feasibility of hypothetical model, improving the hypothetical model,field testing of hypothetical model, and designing of the final model based on counseling collaborative learning. The subjects of this research were students and lecturers. The data was collected using questionnaire and interview and analyzed quantitatively and qualitatively.The results shows that most of the student are in the middle category. It also reveals that the process of learning has not optimally develop students creative thinking ability. Based on the result it was recommended for teachers and counselors to develop students’ creative thinking, to build a harmonious relationship, and to build partnership and collaboration with students.